Phenology of African mahogany plants submitted to irrigation - Casaroli, Derblai; de Oliveira Rosa, Flávio; Alves Júnior, José; Pêgo Evangelista, Adão Wagner (Comunicata Scientiae, 2018)
In the searching of forest species with good wood quality, easy adaptability and high commercial value, the African mahogany (Khaya ivorensis Chev. A.) have been a good alternative. This study aimed evaluate the phenometric responses of African Mahogany submitted to irrigation. The field experiment was carried out in Bonfinópolis-GO, Brazil, with young plants of African mahogany, being 5 irrigated and 5 non-irrigated. The following variables were evaluated: plant height, stem heigh, number of leaves and leaflets, stem diameter and leaf area. A completely randomized design was used in a bi-factorial scheme 2x9 (A: irrigated and non-irrigated; D: 0, 120, 180, 240, 300, 360, 420, 480, 540 days after transplanting). All the variables showed significant differences not only for irrigated and non-irrigated treatments but also for the times of evaluation, except for stem diameter. Irrigation resulted in higher growth of plants and the irrigation of young African mahogany plants should be used mainly in drought period.